Opportunities for antimicrobial stewardship in patients with acute bacterial skin and skin structure infections who are unsuitable for beta-lactam antibiotics: a multicenter prospective observational study. (February 2019) - Sandoe, Jonathan A.T.; Saeed, Kordo; Guleri, Achyut; Hand, Kieran S.; Dillon, Ryan; Allen, Mike; Mayes, Amazigom; Glen, Fiona; Gonzalez-Ruiz, Armando
Purpose: The objective of this prospective, observational study was to describe the treatment, severity assessment and healthcare resources required for management of patients with acute bacterial skin and skin structure infections who were unsuitable for beta-lactam antibiotic treatments. Methods: Patients were enrolled across five secondary care National Health Service hospitals. Eligible patients had a diagnosis of acute bacterial skin and skin structure infection and were considered unsuitable for beta-lactam antibiotics (e.g. confirmed/suspected methicillin-resistant Staphylococcus aureus, beta-lactam allergy). Data regarding diagnosis, severity of the infection, antibiotic treatment and patient management were collected. Results: 145 patients with acute bacterial skin and skin structure infection were included; 79% ( n = 115) patients received greater than two antibiotic regimens; median length of the first antibiotic regimen was 2 days (interquartile range of 1–5); median time to switch from intravenous to oral antibiotics was 4 days (interquartile range of 3–8, n = 72/107); 25% ( n = 10/40) patients with Eron class 1 infection had systemic inflammatory response syndrome, suggesting they were misclassified. A higher proportion of patients with systemic inflammatory response syndrome received treatment in an inpatient setting, and their length of stay was prolonged in comparison with patients without systemic inflammatory response syndrome. Conclusion: There exists an urgent need for more focused antimicrobial stewardship strategies and tools for standardised clinical assessment of acute bacterial skin and skin structure infection severity in patients who are unsuitable for beta-lactam antibiotics. This will lead to optimised antimicrobial treatment strategies and ensure effective healthcare resource utilisation.